Extensive DNA end processing by exo1 and sgs1 inhibits break-induced replication. - Vanessa A Marrero; Lorraine S Symington (PLoS Genetics)
Homology-dependent repair of DNA double-strand breaks (DSBs) by gene conversion involves short tracts of DNA synthesis and limited loss of heterozygosity (LOH). For DSBs that present only one end, repair occurs by invasion into a homologous sequence followed by replication to the end of the chromosome resulting in extensive LOH, a process called break-induced replication (BIR). We developed a BIR assay in Saccharomyces cerevisiae consisting of a plasmid with a telomere seeding sequence separated from sequence homologous to chromosome III by an I-SceI endonuclease recognition site. Following cleavage of the plasmid by I-SceI in vivo, de novo telomere synthesis occurs at one end of the vector, and the other end invades at the homologous sequence on chromosome III and initiates replication to the end of the chromosome to generate a stable chromosome fragment (CF). BIR was infrequent in wild-type cells due to degradation of the linearized vector. However, in the exo1Delta sgs1Delta mutant, which is defective in the 5'-3' resection of DSBs, the frequency of BIR was increased by 39-fold. Extension of the invading end of the plasmid was detected by physical analysis two hours after induction of the I-SceI endonuclease in the wild-type exo1Delta, sgs1Delta, and exo1Delta sgs1Delta mutants, but fully repaired products were only visible in the exo1Delta sgs1Delta mutant. The inhibitory effect of resection was less in a plasmid-chromosome gene conversion assay, compared to BIR, and products were detected by physical assay in the wild-type strain. The rare chromosome rearrangements due to BIR template switching at repeated sequences were increased in the exo1Delta sgs1Delta mutant, suggesting that reduced resection can decrease the fidelity of homologous recombination.